Preparation and testing of cefquinome-loaded poly lactic-co-glycolic acid microspheres for lung targeting. (1st January 2017) - Qu, Shaoqi; Zhao, Li; Zhu, Jiajia; Wang, Chunmei; Dai, Cunchun; Guo, Hui; Hao, Zhihui
Abstract: The aim of this study was to prepare cefquinome-loaded poly lactic-co-glycolic acid (PLGA) microspheres and to evaluate their in vitro and in vivo characteristics. Microspheres were prepared using a spry drier and were characterized in terms of morphology, size, drug-loading coefficient, encapsulation ratio and in vitro release. The prepared microspheres were spherical with smooth surfaces and uniform size (12.4 ± 1.2 μm). The encapsulation efficiency and drug loading of cefquinome was 91.6 ± 2.6 and 18.3 ± 1.3%, respectively. In vitro release of cefquinome from the microspheres was sustained for 36 h. In vivo studies identified the lung as the target tissue and the region of maximum cefquinome release. A partial lung inflammation was observed but disappeared spontaneously as the microspheres were removed through in vivo decay. The sustained cefquinome release from the microspheres revealed its applicability as a drug delivery system that minimized exposure to healthy tissues while increasing the accumulation of therapeutic drug at the target site. These results indicated that the spray-drying method of loading cefquinome into PLGA microspheres is a straightforward method for lung targeting in animals.